An adaptive energy efficient flow coverage scheme for mobile crowd sensing in urban streets. (2018) - Gad-ElRab, Ahmed A.A.; Alsharkawy, Almohammady S.
With the rapid growth of sensor technology, smartphone sensing has become an effective approach to improve the quality of applications in smartphones. Mobile crowd sensing (MCS) is a new paradigm which takes advantage of pervasive smartphones to efficiently collect data in the urban streets. To achieve a good service quality for a MCS application, coverage mechanisms are necessary to achieve the sensing task requirements. The main problem is how to cover all segments in the street sides and select a minimal number of participants in each street segment. To solve this problem, a flow coverage scheme is proposed to cover a specific street. The proposed scheme is based on using a modified localisation method that uses a minimal of GPS sensors and utilises the Zigbee technology to communicate and estimate the distance between nodes. Extensive simulation results well justify the effectiveness and robustness of the proposed scheme.